Perspektif Lembaga Swadaya Masyarakat Lokal dan Pemerintah Daerah Terhadap Sumberdaya Alam (Discourse Analisis dalam Kasus Eksploitasi Pasir di Perairan Krakatau Lampung Selatan) - Ahmad Robi Ulzikri (Jurnal Public Policy, 2020)
South Lampung is one of the areas that still upholds customary and cultural values. Including one of them is in terms of preserving the environment. On the other hand, development in the area continues. However, the development discourse initiated by local governments, both district and provincial, often conflicts with the interests of local communities. One of them is the refusal, such as the local community and non-governmental organizations in the Rajabasa sub-district of South Lampung, against the exploitation of sand in the waters of the Anak Krakatau mountain by a private company that has obtained a permit from the provincial government. This study aims to determine the perspective of local non-governmental organizations and local governments in interpreting the existence of natural resources in the regions. The research method used is qualitative with a discourse analysis approach. Data collection comes from literature studies such as books, journals and news. The results show that the community has a perspective in looking at natural resources in the area, namely that they must maintain the status quo by assessing that natural resources need to be preserved as local wisdom without exploitation while the government assesses natural resources through proper exploration of natural resources. in fact, it can optimize regional income and create welfare for the community